2012
DOI: 10.1111/jfr3.12001
|View full text |Cite
|
Sign up to set email alerts
|

An integrated model system for coastal flood prediction with a case history for Walcott, UK, on 9 November 2007

Abstract: An integrated model system is based on downscaling from climate models, to wave climate and continental shelf models for tides and surge, to coastal models for waves and water levels, to beach levels and overtopping of sea defences and inundation. Present operational practice in the UK is described. The model system is applied to the prediction of flooding at Walcott on 9 November 2007. Inundation levels are predicted in reasonable agreement with those at certain residential properties in Walcott as reported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Typically this is achieved using a numerical modeling approach in which storm-tide conditions of interest, commonly based on a probability of exceedence or ''return period' ' [e.g., Tawn, 1992;Haigh et al, 2010], are imposed upon an inundation model domain boundary [e.g., Bates et al, 2005Bates et al, , 2010, which may incorporate defense responses and be used to assess economic damage [e.g., Dawson et al, 2009]. Resulting flood conditions may be used to infer likely inundation extents and potential losses for specific flood events [e.g., Stansby et al, 2012;Smith et al, 2012;Wadey et al, 2012). These assessments provide a vital tool for informing policy decisions (e.g., cost-benefit of flood defenses; shoreline planning) and scenario-based assessment of coastal change [Dawson et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Typically this is achieved using a numerical modeling approach in which storm-tide conditions of interest, commonly based on a probability of exceedence or ''return period' ' [e.g., Tawn, 1992;Haigh et al, 2010], are imposed upon an inundation model domain boundary [e.g., Bates et al, 2005Bates et al, , 2010, which may incorporate defense responses and be used to assess economic damage [e.g., Dawson et al, 2009]. Resulting flood conditions may be used to infer likely inundation extents and potential losses for specific flood events [e.g., Stansby et al, 2012;Smith et al, 2012;Wadey et al, 2012). These assessments provide a vital tool for informing policy decisions (e.g., cost-benefit of flood defenses; shoreline planning) and scenario-based assessment of coastal change [Dawson et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has primarily been concerned with exploring the impact of a joint probability distribution on inundation extent and flood hazard [17] without comparing the impact of various morphological settings to account for various models that may be applied by coastal managers. Hydrodynamic factors have been applied in a coastal flood forecasting system that parametrised beach levels using canonical correlation analysis (CCA) according to the incident wave conditions [52]. Whilst this may be more computationally efficient over a longer forecasting period, it negates the detailed representation of the time-varying event-driven morphological evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The method relies on prerequisite calculations at regional and local scales of the offshore characteristics of the storm; this downscaling approach is quite similar to the ones used by Pedreros et al (2011) or Stansby et al (2013), with a last step that aims to be more integrative and realistic:…”
Section: Modelling Methodsmentioning
confidence: 99%
“…For example, Stansby et al (2013) calculated an incoming discharge with a 1-D Boussinesq-NLSW hybrid model, and injected them in a 2-D finite elements hydrodynamic model (DEM, spatial resolution varying from 50 to 1 m) to simulate the associated flood in Walcott (UK). They showed that using instantaneous or averaged discharges can significantly impact the simulated water level.…”
Section: Introductionmentioning
confidence: 99%